Renewable Energy Prospects for the European Union (International Renewable Energy Agency (IRENA), 2018)
For more than two decades, the European Union (EU) has been at the forefront of global renewable energy deployment. The adoption of long-term targets and supporting policy measures has resulted in strong growth in renewable energy consumption across the region, from a 9% share in 2005 to 16.7% in 2015. Currently, the EU is on track to meet its 20% target established for 2020. In October 2014, the European Council agreed on a new set of energy and climate targets for the period up to 2030 (European Council, 2014), including a minimum target of 27% for the share of renewable energy consumed in the EU. This agreement was followed by the Energy Union framework strategy of February 2015, which aims to make the EU "the world leader in renewable energy" (European Commission, 2015a). The European Union ratified the Paris Agreement, which established the goal to limit the rise in global temperatures this century to "well below 2°C" compared to pre-industrial levels. In practice, this entails reducing global carbon emissions from energy use to zero by 2060 and maintaining that level until the end of the century. ... For the crucial 2020-2030 period, the European Commission tabled the "Clean Energy for All Europeans" package in November 2016. The package proposes a regulatory framework to support renewable energy deployment (European Commission, 2016a). The International Renewable Energy Agency (IRENA), at the Commission's request, has carried out an assessment of the renewable energy prospects of the European Union to 2030 to support discussion on this proposal. The study, conducted in close collaboration with the Commission, also forms part of REmap - IRENAs' renewable energy roadmap. The resulting REmap EU study aims to identify cost-effective renewable energy options across all Member States, sectors, and technologies, in order to meet - and potentially exceed - the proposed 27% renewables target for 2030
"Based on REmap analysis conducted by the International Renewable Energy Agency in co-operation with the European Commission"--Cover
Keywords: Renewable energy.; Energy systems.; Energy security -- European Union countries.; elektronické knihy; electronic books